Spesifisitas antibodi monokional anti protein ekskretori-sekretori Brugia malayi terhadap protein nematoda lain - Soeyoko, Soeyoko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Previous studies using hybridoma technique had produced monoclonal antibodies against excretory-secretory (ES) protein of B. malayi i.e. Fesi, Fes3, Fes7, Fesl3 and Fesi5. Those monoclonal antibodies will be used to diagnose malayan filariasis in the endemic areas.Objectives: To reveal binding specificities of those monoclonal antibodies to ES protein of B. malayi, heterologous protein i.e. Ascaris lumbricoides, Necator americanus and homologous protein i.e. Brugia pahangi.Methods: Binding specificities of those monoclonal antibodies to other nematodes protein were assessed by ELISA and inhibition ELISA techniques.Result: Those monoclonal antibodies showed different binding specificities profiles. Fesi, Fesi3 and Fes. revealed specific reaction to ES protein of B. malayi but they did not react to heterologous and homologous protein. Fes3 and Fes7 did not reveal binding specificities to heterologous protein but they had low cross-reactivity to homologous protein. Cross-reactivity values of Fes3 and Fes7 were 33.3% and 22% respectively. Conclusion: Monoclonal antibodies against ES protein of B. malayi i.e. Fesi, Fesi3 and Fesl5 revealed specific reaction to ES protein of B. malayi, but Fes3 and Fes7 had low cross-reactivity to protein of B. pahangi.Key words: binding specificity - monoclonal antibody - ES protein - heterolog protein - homolog protein -Â ELISA.